Sole-parent work schedules and adolescent wellbeing: Evidence from Australia - Li, Jianghong; Kendall, Garth; Dockery, Alfred Michael (My University, 2016)
Extensive evidence has shown that working nonstandard hours, such as evening or night shifts, impacts negatively on workers' own health, and a growing literature suggests such impacts extend to the health of workers’ children. Using matched parent and child data from a large Australian panel survey this paper explores the effects of parental work schedules on the mental and physical health of adolescents aged 15–20 in sole-parent families. Random-effects models indicate adolescents have marginally worse emotional and physical health when their parent works nonstandard hours, based on SF-36 component summary scores, associated primarily with emotional or physical role limitations. Parental weekend schedules are particularly detrimental to adolescent physical health. Evidence is found that the effects of nonstandard work schedules on adolescent wellbeing are transmitted through increased work-family conflict and exacerbated where parents have low job control.
Social Science & Medicine
Keywords: Employment -- Hours; Children -- Adolescents and youth; Health -- Wellbeing; Health and wellbeing; Labour market; Children; Employment; Health; Adolescents and youth; Hours; Wellbeing; Employment and unemployment; Health and wellbeing